Emerging roles of keratinocytes in nociceptive transduction and regulation - Xu, Xiaohan; Yu, Catherine; Xu, Li; Xu, Jijun (Frontiers in Molecular Neuroscience, 2022)
Keratinocytes are the predominant block-building cells in the epidermis. Emerging evidence has elucidated the roles of keratinocytes in a wide range of pathophysiological processes including cutaneous nociception, pruritus, and inflammation. Intraepidermal free nerve endings are entirely enwrapped within the gutters of keratinocyte cytoplasm and form en passant synaptic-like contacts with keratinocytes. Keratinocytes can detect thermal, mechanical, and chemical stimuli through transient receptor potential ion channels and other sensory receptors. The activated keratinocytes elicit calcium influx and release ATP, which binds to P2 receptors on free nerve endings and excites sensory neurons. This process is modulated by the endogenous opioid system and endothelin. Keratinocytes also express neurotransmitter receptors of adrenaline, acetylcholine, glutamate, and γ-aminobutyric acid, which are involved in regulating the activation and migration, of keratinocytes. Furthermore, keratinocytes serve as both sources and targets of neurotrophic factors, pro-inflammatory cytokines, and neuropeptides. The autocrine and/or paracrine mechanisms of these mediators create a bidirectional feedback loop that amplifies neuroinflammation and contributes to peripheral sensitization.